Denotative and connotative meaning relations in the selection of canine lexicon in the Spy x Family anime series - Muhammad Yusuf; Muhammad Kiki Wardana (TALENTA, 2026)
This study investigates the denotative and connotative meaning relations of canine terminology in the anime Spy x Family Season 2 Episode 1 (